2012
DOI: 10.1186/cc11895
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind placebo-controlled trial of 40 mg/day of atorvastatin in reducing the severity of sepsis in ward patients (ASEPSIS Trial)

Abstract: IntroductionSeveral observational studies suggest that statins modulate the pathophysiology of sepsis and may prevent its progression. The aim of this study was to determine if the acute administration of atorvastatin reduces sepsis progression in statin naïve patients hospitalized with sepsis.MethodsA single centre phase II randomized double-blind placebo-controlled trial. Patients with sepsis were randomized to atorvastatin 40 mg daily or placebo for the duration of their hospital stay up to a maximum of 28-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
6

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 16 publications
1
102
0
6
Order By: Relevance
“…Evidences suggested that statin therapy reduces six times the incidence in severe sepsis [5], three times developing pneumonia in diabetic patients [68], 2.5 times hospital admission for sepsis in patients with chronic renal failure [69], reduces 7.9 times the developing severe sepsis due to acute bacterial infection [6], reduce 19-25% incidence of sepsis in patients with cardiovascular disease [70]. A recent study also showed that acute atorvastatin administration may prevent sepsis progression in patient with sepsis [71]. However mortality rate didn't reduce by statin using in this study.…”
Section: Evidences For Statin Use In Sepsismentioning
confidence: 99%
“…Evidences suggested that statin therapy reduces six times the incidence in severe sepsis [5], three times developing pneumonia in diabetic patients [68], 2.5 times hospital admission for sepsis in patients with chronic renal failure [69], reduces 7.9 times the developing severe sepsis due to acute bacterial infection [6], reduce 19-25% incidence of sepsis in patients with cardiovascular disease [70]. A recent study also showed that acute atorvastatin administration may prevent sepsis progression in patient with sepsis [71]. However mortality rate didn't reduce by statin using in this study.…”
Section: Evidences For Statin Use In Sepsismentioning
confidence: 99%
“…Statin use prior to the development of multiple organ failure may in part explain the discordance between observational studies (including patients who were on statins before their critical illness) with randomised trials (including patients with established organ failure). Of note a study by Patel et al [14] suggests a lower rate of progression of sepsis with atorvastatin compared to placebo. Fortunately further studies assessing if statin therapy may have a preventive role very early in an illness or even as prophylaxis are now starting.…”
mentioning
confidence: 99%
“…Investigators will have to decide whether the trials should be restricted to ICU-admitted patients, who might not benefit, 76,77,113 or include all hospitalized patients at risk of rapidly developing more serious illness. 79 Regardless of their design, the trials will be expensive, so animal studies comparing different immunomodulatory agents will be needed to guide the choice of which agent(s) to evaluate in clinical trials.…”
Section: Questions About the Effectiveness Of Statins In Treating Infmentioning
confidence: 99%